(untitled) (GEON Journal (Management, Organizations and Business), 2021)
The socioeconomic analysis of the Magical Towns Program (PPM) the municipality of Pinos, Zacatecas, Mexico shows the socioeconomic effects of the PPM. Problem: The implementation of the PPM in the community has generated strategies for economic tourism development with economic benefits to entrepreneurs, authorities and citizens in the community. Objective: To validate the level of contribution of the PPM in economic activities and the relationship with tourism in the municipality of Pinos, Zacatecas, Mexico. Materials and methods: The research has a mixed quantitative and qualitative approach. Citizens of the community were interviewed through a questionnaire with a representative sample of informants. The qualitative approach involved the participation of representatives of the municipal authority. The analysis is carried out by means of the descriptive and causal method. Results and discussion: The study confirms the integral economic tourism development and the benefits with the implementation of the PPM, perceived by the citizens, municipal authority officials, businessmen, in the improvement of the quality of life of the inhabitants and the contribution of the tourism companies in activities of social and cultural responsibility in the community. Conclusion: In the research, the informants confirmed the impact of economic tourism development in the generation of jobs, the offer of tourism products and services, and the valuation and recognition of the resources in the community. It contributes to the socioeconomic analysis in the community evidences the economic tourism development with the implementation of the PPM and the impact of tourism activities in the community.